Wear-resistant anticorrosive paint for hardware fitting surface and preparation method of wear-resistant anticorrosive paint
By using a mixed solution of silicone modified polyester resin and other fillers to form wear-resistant anticorrosion coatings, the problems of fast loss of hot-dip galvanized coatings and surface wear of the metal tool are solved, and the high-efficiency anticorrosion and wear resistance of the metal tool are provided, suitable for On-site construction.
Patent Information
- Application Number
- CN202411521553.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-10
AI Technical Summary
The existing hot-dip galvanized coatings are quickly lost and cannot be repaired in severely polluted environments, resulting in corrosion failure of the metal tool, and the surface of the metal tool is prone to wear and lacks anti-corrosion coatings with good wear resistance.
Using mixed solutions A and B composed of silicone modified polyester resin, silane coupling agent, zinc powder, diamond and molybdenum sulfide, abrasion-resistant anticorrosion coating is formed by stirring and ultrasonic dispersion, and applied to the surface of the metal tool and quickly Curing, providing multi-layered corrosion and wear resistance.
It provides a stable and easy to store and transport wear-resistant anti-corrosion coating, which can be quickly applied to the surface of the metal tool on site, significantly improving the anti-corrosion performance and wear resistance of the coating, extending the service life of the metal tool and reducing safety hazards.
Smart Images

Figure BDA0005108161010000101 
Figure BDA0005108161010000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal anticorrosion, in particular to a wear-resistant anticorrosion coating for the surface of metal fittings and a preparation method thereof. Background Art
[0002] Overhead transmission lines have been exposed to complex outdoor natural environments during their service life, and are affected by complex meteorological factors such as wind, frost, rain and snow, which makes the metal parts in the transmission lines prone to corrosion. Corrosion not only reduces the service life of metal parts in the line, but also brings uncontrollable safety hazards and causes serious safety accidents. Therefore, effective anti-corrosion measures are the key to ensuring the long-term and stable operation of transmission lines, and anti-corrosion work has also become a task in the operation and maintenance of my country's transmission lines.
[0003] Hardware is an important connecting part in the transmission line. It is usually made of metal materials such as steel or aluminum alloy. It is a typical component that needs to be focused on corrosion protection. At present, most of the hardware in my country's transmission lines use hot-dip galvanizing coating for corrosion protection. However, the zinc coating loses very quickly in a heavily polluted environment and the exhaustion time is unpredictable, which will cause the hardware to lose protection and cause accidents related to corrosion failure. At the same time, the hot-dip galvanizing coating on the surface of the hardware cannot be effectively repaired. Therefore, the development of new high-performance anti-corrosion coating materials suitable for on-site coating to replace hot-dip galvanizing coating will be an important direction for the operation and maintenance of power systems. In addition, since the surface of the hardware is prone to wear due to the load during use, further improving the wear resistance of the corrosion-resistant coating on the surface of the hardware also has important application value. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a wear-resistant and anti-corrosion coating for the surface of hardware and a preparation method thereof. The coating has stable components and is easy to store and transport. At the same time, a layer of long-lasting anti-corrosion coating with good wear resistance can be quickly prepared on the surface of the hardware by a variety of processes such as brushing and spraying. The coating of the present invention has a simple and flexible use process and is convenient for on-site construction of power transmission lines of power grids.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a wear-resistant and anti-corrosion coating for the surface of hardware, comprising a mixed solution A and a mixed solution B, wherein the reagents in the mixed solution A include silicone-modified polyester resin, xylene, ethylene glycol, isophorone, a leveling agent, and a defoaming agent, and the reagents in the mixed solution B include silane coupling agent KH560, a polyisocyanate curing agent, ethyl acetate, ethylene glycol, dibutyltin dilaurate, zinc powder, diamond, and molybdenum sulfide.
[0006] A further improvement of the technical solution of the present invention is that the mass percentages of the reagents contained in the mixed solution A are: 48% to 54.5% silicone-modified polyester resin, 8% to 9% xylene, 26% to 28% ethylene glycol, 10% to 12% isophorone, 1% to 2% leveling agent, and 0.5% to 1% defoaming agent, and the total mass percentage of all the above reagents is 100%.
[0007] A further improvement of the technical solution of the present invention is that the mass percentages of the reagents contained in the mixed solution B are: 20% to 21% ethyl acetate, 44% to 50% ethylene glycol, 7% to 8% silane coupling agent KH560, 14% to 15% polyisocyanate curing agent, 3% to 4% dibutyltin dilaurate, 5% to 6% zinc powder, 0.5% to 1% diamond, and 0.5% to 1% molybdenum sulfide, and the total mass percentage of all the above reagents is 100%.
[0008] A further improvement of the technical solution of the present invention is that the diamond powder adopts micron-level specifications and the molybdenum sulfide powder adopts nanometer-level specifications.
[0009] A further improvement of the technical solution of the present invention is that the zinc powder in the mixed solution B has a specification of 200 mesh, the diamond has a specification of 800 mesh, and the particle size of molybdenum sulfide is 50-200 nm.
[0010] A further improvement of the technical solution of the present invention is: a method for preparing a wear-resistant and anti-corrosion coating for a metal fitting surface, comprising the following steps:
[0011] Step S1, mixed solution A: a certain amount of organosilicon-modified polyester resin, xylene, ethylene glycol, isophorone, leveling agent, and defoaming agent are placed in a container and stirred to form a mixed solution;
[0012] Step S2, mixed solution B: a certain amount of silane coupling agent KH560, polyisocyanate curing agent, ethyl acetate, ethylene glycol, dibutyltin dilaurate, zinc powder, diamond, and molybdenum sulfide are placed in a container and stirred to form a dispersion;
[0013] Step S3: Before using the coating, the mixed solution A and the mixed solution B are stirred evenly respectively, and then mixed in a mass ratio of 1:0.6-0.8. After mixing, they are stirred evenly again and subjected to ultrasonic dispersion treatment, and then applied to the surface of the hardware and subjected to rapid curing treatment.
[0014] A further improvement of the technical solution of the present invention is that: in step S3, the mixed solution A and the mixed solution B are stirred evenly again after mixing and the ultrasonic dispersion treatment is completed within 30 minutes.
[0015] A further improvement of the technical solution of the present invention is that in step S3, the mixed solution A and the mixed solution B are mixed.
[0016] A further improvement of the technical solution of the present invention is that in step S3, the surface of the hardware needs to be pre-treated by grinding and rust removal.
[0017] A further improvement of the technical solution of the present invention is that the rapid curing treatment in step S3 is to use hot air from a hair dryer to promote curing, and the time is about 20 to 40 minutes.
[0018] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is:
[0019] 1. The coating of the present invention is prepared by mixing a mixed solution A and a mixed solution B. The mixed solution A and the mixed solution B are chemically stable and easy to store and transport;
[0020] 2. Zinc powder is added to the coating formula of the present invention, and the zinc powder can act as a sacrificial anode to provide cathodic protection, play a role in rust prevention, and improve the anti-corrosion performance of the coating;
[0021] 3. The coating formula of the present invention adds micron-level diamond powder and nano-level molybdenum sulfide powder, which can further improve the anti-corrosion performance and wear resistance of the coating. Among them, the micron-level diamond powder can serve as a hard reinforcement phase to improve the strength of the coating, and the nano-level molybdenum sulfide powder plays a role in reducing the friction coefficient of the coating. The reinforcement phase of the micro / nano multi-level structure can effectively improve the wear resistance of the coating.
[0022] 4. The coating of the present invention can be applied to the surface of the hardware by various processes such as leveling, brushing, and spraying to quickly solidify and form a wear-resistant and anti-corrosion coating. The coating preparation process is simple and flexible, and can be conveniently applied to on-site construction of power transmission lines in power grids. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with embodiments:
[0024] The present invention provides a wear-resistant and anti-corrosion coating for the surface of metal fittings, comprising a mixed solution A and a mixed solution B, wherein the reagents in the mixed solution A include an organosilicon-modified polyester resin, xylene, ethylene glycol, isophorone, a leveling agent, and a defoaming agent. Among them, the organosilicon-modified polyester resin is the main anti-corrosion material. Xylene is a diluent for anti-corrosion paint. Ethylene glycol and isophorone are solvents. The leveling agent and the defoaming agent are film-forming aids to improve the film-forming quality of the anti-corrosion coating. The reagents in the mixed solution B include a silane coupling agent KH560, a polyisocyanate curing agent, ethyl acetate, ethylene glycol, dibutyltin dilaurate, zinc powder, diamond, and molybdenum sulfide. Among them, the silane coupling agent KH560 is a filler surface modifier, which improves the wettability and dispersibility of the filler in the coating. The polyisocyanate curing agent promotes the curing of the coating into an anti-corrosion coating. Dibutyltin dilaurate is a curing reaction accelerator, which improves the curing speed and coating quality of the anti-corrosion coating. Zinc powder, diamond and molybdenum sulfide are all fillers. Zinc powder can provide cathodic protection as a sacrificial anode, play a role in rust prevention, and improve the anti-corrosion performance of the coating. Diamond and molybdenum sulfide can improve the corrosion resistance and wear resistance of the coating. Ethyl acetate and ethylene glycol are solvents. The chemical properties of mixed solution A and mixed solution B are stable, which is convenient for storage and transportation; the coating can be applied to the surface of the hardware by leveling, brushing, spraying and other processes to quickly solidify and generate a wear-resistant and anti-corrosion coating. The preparation process of the coating is simple and flexible, which is convenient for on-site construction of power transmission lines in power grids.
[0025] Among them, the mass percentages of reagents contained in the mixed solution A are: 48% to 54.5% silicone-modified polyester resin, 8% to 9% xylene, 26% to 28% ethylene glycol, 10% to 12% isophorone, 1% to 2% leveling agent, and 0.5% to 1% defoaming agent, and the total mass percentage of all the above reagents is 100%.
[0026] The mass percentages of reagents contained in the mixed solution B are: 20% to 21% ethyl acetate, 44% to 50% ethylene glycol, 7% to 8% silane coupling agent KH560, 14% to 15% polyisocyanate curing agent, 3% to 4% dibutyltin dilaurate, 5% to 6% zinc powder, 0.5% to 1% diamond, and 0.5% to 1% molybdenum sulfide, and the total mass percentage of all the above reagents is 100%.
[0027] The diamond powder in the present invention adopts micron-level specifications, and the molybdenum sulfide powder adopts nano-level specifications. The coating formula of the present invention adds micron-level diamond powder and nano-level molybdenum sulfide powder, which can further improve the corrosion resistance of the coating and improve the wear resistance of the coating. Among them, the micron-level diamond powder can be used as a hard reinforcing phase to improve the strength of the coating, and the nano-level molybdenum sulfide powder plays a role in reducing the friction coefficient of the coating. The reinforcing phase of the micro / nano multi-level structure can effectively improve the wear resistance of the coating. The zinc powder specification selected in the mixed solution B is preferably 200 mesh, the diamond specification is preferably 800 mesh, and the particle size of the molybdenum sulfide is preferably 50-200nm.
[0028] The present invention also provides a method for preparing a wear-resistant and anti-corrosion coating for a metal fitting surface, comprising the following steps:
[0029] Step S1, mixed solution A: a certain amount of organosilicon-modified polyester resin, xylene, ethylene glycol, isophorone, leveling agent, and defoaming agent are placed in a container and stirred to form a mixed solution;
[0030] Step S2, mixed solution B: a certain amount of silane coupling agent KH560, polyisocyanate curing agent, dibutyltin dilaurate, zinc powder, diamond, molybdenum sulfide, and ethyl acetate are placed in a container and stirred to form a dispersion;
[0031] Step S3, before using the coating, stir the mixed solution A and the mixed solution B respectively, and then mix them in a mass ratio of 1:0.6-0.8. After mixing, stir them again and perform ultrasonic dispersion treatment, and then apply them to the surface of the hardware for rapid curing treatment. The rapid curing treatment is to use a hair dryer to blow dry with hot air to promote curing, and the time is about 20-40 minutes. Prior to this, the surface of the hardware needs to be pre-treated by grinding and rust removal. After mixing the mixed solution A and the mixed solution B, stir them again and perform ultrasonic dispersion treatment, and the time is controlled to be completed within 30 minutes.
[0032] Example 1
[0033] 51% of silicone-modified polyester resin, 8.5% of xylene, 27% of ethylene glycol, 11% of isophorone, 1.5% of leveling agent and 1% of defoaming agent were mixed uniformly to prepare a mixed solution A; 21% of ethyl acetate, 45.6% of ethylene glycol, 8% of silane coupling agent KH560, 14.5% of polyisocyanate curing agent, 3.5% of dibutyltin dilaurate, 6% of zinc powder, 0.8% of diamond and 0.6% of molybdenum sulfide were mixed uniformly to prepare a mixed solution B.
[0034] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.7, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing, which took about 20 minutes.
[0035] Example 2
[0036] 54.5% of silicone-modified polyester resin, 8% of xylene, 26% of ethylene glycol, 10% of isophorone, 1% of leveling agent, and 0.5% of defoaming agent were mixed uniformly to prepare a mixed solution A; 20% of ethyl acetate, 50% of ethylene glycol, 7% of silane coupling agent KH560, 14% of polyisocyanate curing agent, 3% of dibutyltin dilaurate, 6% of zinc powder, 1% of diamond, and 1% of molybdenum sulfide were mixed uniformly to prepare a mixed solution B.
[0037] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.8, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing, which took about 30 minutes.
[0038] Example 3
[0039] 48% of silicone-modified polyester resin, 9% of xylene, 28% of ethylene glycol, 12% of isophorone, 2% of leveling agent and 1% of defoaming agent were mixed uniformly to prepare a mixed solution A; 21% of ethyl acetate, 44% of ethylene glycol, 8% of silane coupling agent KH560, 15% of polyisocyanate curing agent, 4% of dibutyltin dilaurate, 5% of zinc powder, 0.5% of diamond and 0.5% of molybdenum sulfide were mixed uniformly to prepare a mixed solution B.
[0040] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.6, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing, which took about 10 minutes.
[0041] Comparative Example 1
[0042] Compared with Example 1, 51% of silicone-modified polyester resin, 8.5% of xylene, 27% of ethylene glycol, 11% of isophorone, 1.5% of leveling agent and 1% of defoaming agent were mixed uniformly to prepare a mixed solution A; 21% of ethyl acetate, 45.6% of ethylene glycol, 8% of silane coupling agent KH560, 14.5% of polyisocyanate curing agent, 3.5% of dibutyltin dilaurate, 6% of zinc powder, 0.8% of diamond and 0.6% of molybdenum sulfide were mixed uniformly to prepare a mixed solution B.
[0043] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.5, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing. However, the curing effect was not good and the resulting coating surface was uneven.
[0044] Comparative Example 2
[0045] Comparative Example 1, 51% of silicone modified polyester resin, 8.5% of xylene, 27% of ethylene glycol, 11% of isophorone, 1.5% of leveling agent, and 1% of defoaming agent were mixed to prepare a mixed solution A; 21% of ethyl acetate, 45.6% of ethylene glycol, 8% of silane coupling agent KH560, 14.5% of polyisocyanate curing agent, 3.5% of dibutyltin dilaurate, 6% of zinc powder, 0.8% of diamond, and 0.6% of molybdenum sulfide were mixed to prepare a mixed solution B.
[0046] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.9, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing. The curing time was 10 minutes, and the resulting coating surface was uneven and had obvious cracks.
[0047] Comparative Example 3
[0048] Comparative Example 2, 54.5% of silicone modified polyester resin, 8% of xylene, 26% of ethylene glycol, 10% of isophorone, 1% of leveling agent, and 0.5% of defoaming agent were mixed to prepare a mixed solution A; 20% of ethyl acetate, 50% of ethylene glycol, 7% of silane coupling agent KH560, 14% of polyisocyanate curing agent, 3% of dibutyltin dilaurate, 7% of zinc powder, 1% of diamond, and 1% of molybdenum sulfide were mixed to prepare a mixed solution B.
[0049] Then, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.8. After 20 minutes of ultrasonic dispersion, there was still a small amount of powder precipitation at the bottom of the coating. The coating was then brushed on the surface of the hardware and dried with hot air from a hair dryer to promote curing, which took about 30 minutes.
[0050] Comparative Example 4
[0051] In comparative example 3, 48% of silicone-modified polyester resin, 9% of xylene, 28% of ethylene glycol, 12% of isophorone, 2% of a leveling agent, and 1% of a defoaming agent were uniformly mixed to prepare a mixed solution A; 21% of ethyl acetate, 44% of ethylene glycol, 8% of a silane coupling agent KH560, 15% of a polyisocyanate curing agent, 4% of dibutyltin dilaurate, 0.5% of diamond, and 0.5% of molybdenum sulfide were uniformly mixed to prepare a mixed solution B.
[0052] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.6, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing, which took about 10 minutes.
[0053] Comparative Example 5
[0054] In comparative example 2, 54.5% of silicone-modified polyester resin, 8% of xylene, 26% of ethylene glycol, 10% of isophorone, 1% of a leveling agent, and 0.5% of a defoaming agent were uniformly mixed to prepare a mixed solution A; 20% of ethyl acetate, 50% of ethylene glycol, 7% of a silane coupling agent KH560, 14% of a polyisocyanate curing agent, 3% of dibutyltin dilaurate, 6% of zinc powder, 2% of diamond, and 1% of molybdenum sulfide were uniformly mixed to prepare a mixed solution B.
[0055] Then, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.8. After 20 minutes of ultrasonic dispersion, there was still a small amount of powder precipitation at the bottom of the coating due to excessive diamond filler. The coating was then brushed on the surface of the hardware and dried with hot air from a hair dryer to promote curing, which took about 30 minutes.
[0056] Comparative Example 6
[0057] In comparative example 3, 48% of silicone-modified polyester resin, 9% of xylene, 28% of ethylene glycol, 12% of isophorone, 2% of a leveling agent, and 1% of a defoaming agent were uniformly mixed to prepare a mixed solution A; 21% of ethyl acetate, 44% of ethylene glycol, 8% of a silane coupling agent KH560, 15% of a polyisocyanate curing agent, 4% of dibutyltin dilaurate, 5% of zinc powder, and 0.5% of molybdenum sulfide were uniformly mixed to prepare a mixed solution B.
[0058] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.6, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing, which took about 10 minutes.
[0059] Comparative Example 7
[0060] Comparative Example 2, 54.5% of silicone modified polyester resin, 8% of xylene, 26% of ethylene glycol, 10% of isophorone, 1% of leveling agent, and 0.5% of defoaming agent were mixed to prepare a mixed solution A; 20% of ethyl acetate, 50% of ethylene glycol, 7% of silane coupling agent KH560, 14% of polyisocyanate curing agent, 3% of dibutyltin dilaurate, 6% of zinc powder, 1% of diamond, and 2% of molybdenum sulfide were mixed to prepare a mixed solution B.
[0061] Then, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.8. After 20 minutes of ultrasonic dispersion, there was still a small amount of powder precipitation at the bottom of the coating due to excessive zinc powder filler. The coating was then brushed on the surface of the hardware and dried with hot air from a hair dryer to promote curing, which took about 30 minutes.
[0062] Comparative Example 8
[0063] In comparative example 3, 48% of silicone-modified polyester resin, 9% of xylene, 28% of ethylene glycol, 12% of isophorone, 2% of a leveling agent, and 1% of a defoaming agent were uniformly mixed to prepare a mixed solution A; 21% of ethyl acetate, 44% of ethylene glycol, 8% of a silane coupling agent KH560, 15% of a polyisocyanate curing agent, 4% of dibutyltin dilaurate, 5% of zinc powder, and 0.5% of diamond were uniformly mixed to prepare a mixed solution B.
[0064] Subsequently, the mixed solution A and the mixed solution B were evenly mixed in a mass ratio of 1:0.6, and after ultrasonic dispersion for 20 minutes, they were brushed on the surface of the hardware, and dried with hot air from a hair dryer to promote curing, which took about 10 minutes.
[0065] The coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were subjected to corresponding performance tests, and the test results are shown in Appendix 1:
[0066] In control example 1, the mass ratio of mixed solution A and mixed solution B was reduced and mixed evenly. The coating had a sticky and uneven appearance, and the adhesion reached level 3. The coating surface blistered during the water resistance test, and the coating surface blistered and rusted during the salt resistance test. The abrasion loss weight of the wear resistance test was 98 mg / 500 r.
[0067] In control example 2, the mass ratio of mixed solution A and mixed solution B was increased and mixed evenly, the coating had peeling and slight bubbles on the surface, and the adhesion reached level 4. The coating surface fell off during the water resistance test, fell off and rusted during the salt resistance test, and the abrasion loss weight of the wear resistance test was 132 mg / 500 r.
[0068] In control example 3, the zinc powder was excessive, and the excessive filler caused precipitation in the coating, the coating surface was uneven, the adhesion reached level 2, and the wear loss weight of the wear resistance test was 77mg / 500r;
[0069] In control example 4, no zinc powder was added, and the coating surface was slightly rusted during the salt resistance test, and the wear loss weight in the wear resistance test was 32 mg / 500 r;
[0070] In control example 5, the diamond filler is excessive, and the excessive filler causes precipitation in the coating, the coating appearance is uneven, and the adhesion reaches level 3. The coating surface is slightly bubbling in the water resistance test, and the coating surface is slightly bubbling and slightly rusted in the salt resistance test. The wear loss weight in the wear resistance test is 59mg / 500r;
[0071] In control example 6, no diamond filler was added, the hardness of the coating was reduced, and the wear loss weight in the wear resistance test was 65 mg / 500 r;
[0072] In control example 7, there is too much molybdenum sulfide filler, and the excessive filler causes precipitation in the coating, the coating appearance is uneven, the adhesion reaches level 2, the coating surface is slightly bubbling during the water resistance test, the coating surface is slightly bubbling during the salt resistance test, and the wear loss weight of the wear resistance test is 43mg / 500r;
[0073] In Control Example 8, no molybdenum sulfide filler was added, and the wear resistance of the coating was reduced. The wear loss weight in the wear resistance test was 48 mg / 500 r.
[0074] The test results of the embodiments are significantly better than those of the control examples in terms of corrosion resistance and wear resistance. The coatings of Examples 1 to 3 all have a smooth appearance without bubbles, and the adhesion reaches level 1. When the water resistance is greater than 240 hours, the coating surface does not bubble or fall off, and when the salt water resistance is greater than 3% NaCl, the coating surface does not bubble or rust when it is greater than 168 hours. The wear loss weight of the wear resistance test is less than 20 mg / 500 r.
[0075] Table 1 Test results of embodiments and control examples
[0076]
[0077]
[0078] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.
[0079] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention still fall within the scope of protection of the technical solutions of the present invention.
Claims
1. A wear-resistant and anti-corrosion coating for the surface of hardware, characterized in that: The invention comprises a mixed solution A and a mixed solution B, wherein the reagents in the mixed solution A comprise organosilicon-modified polyester resin, xylene, ethylene glycol, isophorone, a leveling agent, and a defoaming agent, and the reagents in the mixed solution B comprise silane coupling agent KH560, a polyisocyanate curing agent, ethyl acetate, ethylene glycol, dibutyltin dilaurate, zinc powder, diamond, and molybdenum sulfide.
2. The wear-resistant and anti-corrosion coating for the surface of metal fittings according to claim 1, characterized in that: The mass percentages of the reagents contained in the mixed solution A are: 48% to 54.5% of silicone-modified polyester resin, 8% to 9% of xylene, 26% to 28% of ethylene glycol, 10% to 12% of isophorone, 1% to 2% of leveling agent, and 0.5% to 1% of defoaming agent, and the total mass percentage of all the above reagents is 100%.
3. The wear-resistant and anti-corrosion coating for the surface of metal fittings according to claim 1, characterized in that: The mass percentages of the reagents contained in the mixed solution B are: 20% to 21% ethyl acetate, 44% to 50% ethylene glycol, 7% to 8% silane coupling agent KH560, 14% to 15% polyisocyanate curing agent, 3% to 4% dibutyltin dilaurate, 5% to 6% zinc powder, 0.5% to 1% diamond, and 0.5% to 1% molybdenum sulfide, and the total mass percentage of all the above reagents is 100%.
4. The wear-resistant and anti-corrosion coating for the surface of metal fittings according to claim 3, characterized in that: The diamond powder is of micron-level specifications, and the molybdenum sulfide powder is of nanometer-level specifications.
5. The wear-resistant and anti-corrosion coating for the surface of metal fittings according to claim 4, characterized in that: The zinc powder in the mixed solution B has a size of 200 mesh, the diamond has a size of 800 mesh, and the particle size of molybdenum sulfide is 50-200 nm.
6. A method for preparing a wear-resistant and anti-corrosion coating for the surface of hardware, characterized in that: The steps include: Step S1, mixed solution A: a certain amount of organosilicon-modified polyester resin, xylene, ethylene glycol, isophorone, leveling agent, and defoaming agent are placed in a container and stirred to form a mixed solution; Step S2, mixed solution B: a certain amount of silane coupling agent KH560, polyisocyanate curing agent, ethyl acetate, ethylene glycol, dibutyltin dilaurate, zinc powder, diamond, and molybdenum sulfide are placed in a container and stirred to form a dispersion; Step S3: Before using the coating, the mixed solution A and the mixed solution B are stirred evenly respectively and then mixed. After mixing, they are stirred evenly again and subjected to ultrasonic dispersion treatment. Subsequently, they are applied to the surface of the hardware and then subjected to rapid curing treatment.
7. The method for preparing a wear-resistant and anti-corrosion coating for the surface of hardware according to claim 6, characterized in that: In the step S3, after the mixed solution A and the mixed solution B are mixed, they are stirred evenly again and subjected to ultrasonic dispersion treatment, which is completed within 30 minutes.
8. A method for preparing a wear-resistant and anti-corrosion coating for a metal fitting surface according to claim 6, characterized in that: In step S3, the mixed solution A and the mixed solution B are mixed in a mass ratio of 1:0.6-0.
8.
9. The method for preparing a wear-resistant and anti-corrosion coating for the surface of hardware according to claim 6, characterized in that: In step S3, the surface of the hardware needs to be pre-treated by grinding and rust removal.
10. The method for preparing the wear-resistant and anti-corrosion coating for the surface of metal fittings according to claim 6, characterized in that: The rapid curing process in step S3 is to use a hair dryer to blow hot air to promote curing, and the time is about 20 to 40 minutes.
Citation Information
Patent Citations
Wear-resistant self-lubricating anticorrosive coating material, preparation method and applications thereof
CN109836959A
Wear-resistant epoxy resin coating and preparation method thereof
CN113088162A